The Effects of Once-Weekly Alendronate 70 mg, Risedronate 35 mg and Raloxifene 60 mg Daily in the Treatment of Postmenopausal Osteoporosis in Turkish Population - Öktem, Mesut; Esinler, İbrahim and Eroğlu, Derya and Akkaya, Pınar and Kuşcu, Esra and Zeyneloğlu, Hulusi (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: We aimed to compare the efficacy and tolerability of once-weekly alendronate 70 mg/weekly, risedronate 35 mg/weekly and raloxifene 60 mg/daily in the treatment of postmenopausal osteoporosis. STUDY DESIGN: Retrospective case-control study. 216 aged matched postmenopausal women with osteoporosis who received alendronate (n=70), risedronate (n=74), or raloxifene (n=72) for 24 months were retrospectively evaluated. Additionally, all patients received 600 mg Calcium+ 400 IU Vit D daily. Bone mineral density (BMD) was measured by dual X-ray absorptiometry. T scores at baseline and 24 months were evaluated in the lumbar spine, total hip, femur neck, and trochanter. RESULTS: Baseline T scores of each region were not significantly different among three groups. T scores increased in the lumbar spine (p<0.01), femur neck (p<0.05), trochanter (p<0.01) and total hip (p<0.05) following 24 months of alendronate treatment. In the risedronate group, there was a significant increase in the lumbar spine only (p<0.01). Raloxifene treatment did not change T scores of any regions. There was only one case (1.4%) with fracture of forearm in the alendronate group. However, in the risedronate group, 5 cases (6.7%) with fracture (one case of elbow, two cases of finger, one case of hip and one cases of vertebral fractures) were seen during the treatment period. In the raloxifene group, 5 cases (6.9%) of bone fracture (including, three cases of fracture of forearm and one case of hip and one case of vertebral fracture) were seen. The rates of fracture and adverse effects in three groups were comparable. CONCLUSİONS: Alendronate 70 mg/weekly was well tolerated and produced significantly greater increases in BMD than other drugs with low fracture incidence.